THE ROLE OF GOVERNMENT AND PRIVATE SECTOR IN DEVELOPING MULTISECTORAL EDUCATION: LITERATURE REVIEW AND RECOMMENDATIONS - Loso Judijanto; Rinovian Rais; Tanwir (International Journal of Teaching and Learning, 2026)
This research aims to explore the collaborative role between the government and the private sector in developing multisectoral education. Through a comprehensive literature analysis, this article identifies how both parties can complement each other in providing education that is more responsive, inclusive and relevant to global dynamics. The government acts as a policy setter and basic infrastructure provider, while the private sector introduces innovation and flexibility and ensures linkages between the education curriculum and labour market needs. The results show that effective communication and a clear partnership framework are essential to align the objectives of both parties. In addition, the development of continuous evaluation and feedback mechanisms is necessary to monitor and improve the quality of co-operation. With the implementation of these strategies, collaboration between the government and the private sector has great potential to create an adaptive, comprehensive and sustainable education system, capable of facing future challenges and opportunities.